Performance evaluation of the Sun Fire Link SMP clusters. (2nd May 2007) - Qian, Ying; Afsahi, Ahmad; Fredrickson, Nathan R.; Zamani, Reza
The interconnection networks and the communication system software are critical in achieving high performance in clusters. Sun Fire Link interconnect is a memory-based interconnect, where the Sun MPI uses the Remote Shared Memory (RSM) model for its user-level inter-node messaging. This paper presents the overall architecture of the Sun Fire Link and its messaging layer. We provide an in-depth performance evaluation of a Sun Fire Link cluster at the RSM, MPI, and application layers. The MPI ping-pong latency and bandwidth are five microseconds and 660 MB/s, respectively. In general, the Sun Fire Link cluster performs relatively well in most cases.